A Goy Who Speaks Yiddish : Christians and the Jewish Language in Early Modern Germany. - Elyada, Aya (Stanford Studies in Jewish History and C., 2012)
This book explores the unique phenomenon of Christian engagement with Yiddish language and literature from the beginning of the sixteenth century to the late eighteenth century. By exploring the motivations for Christian interest in Yiddish, and the differing ways in which Yiddish was discussed and treated in Christian texts, A Goy Who Speaks Yiddish addresses a wide array of issues, most notably Christian Hebraism, Protestant theology, early modern Yiddish culture, and the social and cultural history of language in early modern Europe. Elyada's analysis of a wide range of philological and theo.